Nursing diagnoses in patients with chronic venous ulcer: observational study - Glycia de Almeida Nogueira; Beatriz Guitton Renaud Baptista Oliveira; Rosimere Ferreira Santana; Ana Carla Dantas Cavalcanti (Universidade Federal de Goias, 2015)
This study aimed to analyze nursing diagnoses in people with chronic venous ulcer. An observational, descriptive, quantitative research conducted in an ambulatory specialized in wound treatment, with a non-probabilistic sample of 20 patients.  Data collection was performed in an institutional form denominated Assessment Protocol for Clients with Tissue Lesions. Diagnoses were established by consensus among four researchers with experience in nursing diagnoses and wound treatments. From data analysis, 16 diagnoses were identified, with 100% of participants presenting: Impaired tissue integrity, Ineffective peripheral tissue perfusion, Risk of infection, Impaired physical mobility and Ineffective health self-control. These diagnoses are found in Safety/Protection, Activity/Rest and Health promotion domains, which from the clinical practice stand point should be priority focuses in nursing intervention and assessment.